Where is community psychology in South African psychology? A knowledge-based perspective - Graham, Tanya M. (PINS-Psychology in Society, 2022)
Prior to 1994 community psychologists played a significant role in South African psychology as a distinct critically oriented grouping advocating for social change. However, the more widespread endorsement of social justice principles in the democratic period shifted the focus of many community-oriented psychologists to participating in more widespread national transformation initiatives. This article highlights changes in the knowledge landscape of community psychology through a comparative analysis of articles published in the SAJP and PINS from 2000 and 2009. This analysis synthesises authorship trends, article types, participants and preferred methods from this corpus. Trends in published work illustrate the shifts and tensions in community psychology in relation to psychology. The article underlines the importance of reconfiguring community psychology to provide a critical, reflexive lens on psychological theory and practice, and considers emergent issues for community psychologists in post-apartheid South Africa.